2021
DOI: 10.1186/s13244-021-01126-y
|View full text |Cite
|
Sign up to set email alerts
|

Using amide proton transfer-weighted MRI to non-invasively differentiate mismatch repair deficient and proficient tumors in endometrioid endometrial adenocarcinoma

Abstract: Objectives To investigate the utility of three-dimensional (3D) amide proton transfer-weighted (APTw) imaging to differentiate mismatch repair deficient (dMMR) and mismatch repair proficient (pMMR) tumors in endometrioid endometrial adenocarcinoma (EEA). Methods Forty-nine patients with EEA underwent T1-weighted imaging, T2-weighted imaging, 3D APTw imaging, and diffusion-weighted imaging at 3 T MRI. Image quality and measurement confidence of APTw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…In previous studies, Tian et al [7] have demonstrated the value of APTw in differentiating stage IA endometrial cancer from endometrial polyps with a diagnostic efficacy of 0.850. In addition, several studies have shown [27][28][29][30] that APTw is valuable for differentiating benign and malignant endometrial disease, assessing Ki-67 expression, preoperative risk assessment, and evaluating microsatellite instability status.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, Tian et al [7] have demonstrated the value of APTw in differentiating stage IA endometrial cancer from endometrial polyps with a diagnostic efficacy of 0.850. In addition, several studies have shown [27][28][29][30] that APTw is valuable for differentiating benign and malignant endometrial disease, assessing Ki-67 expression, preoperative risk assessment, and evaluating microsatellite instability status.…”
Section: Discussionmentioning
confidence: 99%
“…Respiratory motion artifact is one of the crucial factors affecting the quality of abdominal MRIs. [10][11][12] In the current exploration stage of the abdominal application of APTw imaging, a few studies promoted the development of technology. Seo et al 10 demonstrated a success rate of 66% for the 3D-APTw imaging of the liver with an ICC of 0.76 (95% CI, 0.63-0.85).…”
Section: Discussionmentioning
confidence: 99%
“…Respiratory motion artifact is one of the crucial factors affecting the quality of abdominal MRIs 10–12 . In the current exploration stage of the abdominal application of APTw imaging, a few studies promoted the development of technology.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations